Effects of use of matlab mathematical software on the academic performance of a group of repeating students of basic mathematics - Surichaqui Gutierrez, Franklin (2020)
In the training of University students, the effect of the use of Matlab software on academic performance has been evaluated in a group of repeating students of basic mathematics, quasi-experimental, quantitative research with a pre-experimental pre-test research design - post test with a single group; There was a sample of 48 repeating students distributed in a single group, using individual academic performance on the scale of 0 to 20; It is concluded that the use of Matlab mathematical software positively influences the academic performance of a group of repeating students